Bioactive potential of Aphanamixis polystachya seed extracts - Banik, SK; Iftekhar, S; Rahman, AFMM; Bari, ML; Islam, MS (Bangladesh Journal of Scientific and Industrial Research, 2021)
Aphanamixis polystachy seed extracts were examined for their in-vitro biological activities. The n-hexane and methanol extract showed significant phenolic content of 12.0 and 11.7 mg GAE/g, respectively. Antioxidant activity was exhibited by the methanol extract (IC50: 22.34 μg/mL) and moderate activity was shown by the n-hexane extract (IC50: 63.05 μg/ml) compared to BHT (tert-butyl-1- hydroxy toluene, IC50: 14.01 μg/ml) though both extracts caused moderate clot lysis of 18.84% and 23.49% compared to the positive control Streptokinase (65.16%). The n-hexane and methanol extract had shown 18.2% and 32.2% inhibition of hypnotic solution induced haemolysis respectively, while the n-hexane extract had almost no activity (2.21%) and methanol extract showed very high (70.17%) inhibition of heat induced haemolysis compared to acetyl salicylic acid (71.9%). Sensible and substantial cytotoxicity was exhibited by the n-hexane (LC50:13.45 μg/ml) and methanol extracts (LC50:1.61 μg/ml), respectively compared to vincristine sulfate (LC50: 0.45 μg/ml). The n-hexane extract showed no antimicrobial activity against the tested micro-organisms but the methanol extract showed a strong zone of inhibition (25 mm) against Staphylococcus aureus and a moderate zone of inhibition (10mm) against Shigella boydii. Both the extracts exhibited almost zero haemolysis. Bangladesh J. Sci. Ind. Res.56(2), 75-86, 2021